Developing a system of sustainability indicators for the Lake Balaton region - Pintér, László; Bizikova, Livia; Kutics, Károly; Vári, Anna (TÁJÖKOLÓGIAI LAPOK, 2008)
Studied area is the Lake Balaton region, where we had to go back to re-clarify issues as we were trying to find suitable indicators. This initiative showed that developing an indicator system is a fairly demanding process. However, indentifying local trends and linking them to policy-making are crucial, because lack of comprehensive information accessible in a timely manner can severely constrain successful adaptation efforts. Although our work represents only an initial step, the indicator system developed in the project will hopefully inspire concerned citizens and organizations in the region to take interest in this issue and continue working on indicators beyond this project.